Undang-Undang Cipta Kerja dalam Hukum Tanah Indonesia - Daniel Romi Sihombing; Denissa Angela Sihombing (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Regulations related to facilitating, protecting and empowering cooperatives and micro, small and medium enterprises, improving the investment ecosystem, and accelerating national strategic projects, including increasing worker protection and welfare spread across various sector laws are currently unable to meet needs. laws to accelerate job creation so that changes need to be made and adjustments to various regulatory aspects related to improving the investment ecosystem, facilitating and accelerating national strategic projects oriented towards national interests based on national science and technology guided by the ideology of Pancasila.